Work Stress, Job Satisfaction, and Motivation on Teacher Performance: Stres Kerja, Kepuasan Kerja, dan Motivasi terhadap Kinerja Guru - Asfirotul Cahyani; Hasan Ubaidillah (Academia Open, 2023)
The general background increasing demands placed on educators necessitate a comprehensive understanding of the factors affecting their performance. While stress, job satisfaction, and work motivation are acknowledged as critical components of teacher effectiveness, existing research shows mixed findings regarding their individual and collective contributions to teaching performance. This study addresses the knowledge gap by examining the relationships between these variables in the context of educators at a specific institution. The primary aim is to determine how work stress, job satisfaction, and work motivation collectively influence teacher performance. Using quantitative methods and a survey distributed to a sample of teachers, data were analyzed through multiple linear regression. Results indicate that, while no significant individual effects of work stress, job satisfaction, or work motivation on teacher performance were found, a significant collective effect was observed. This suggests that simultaneous variations in these factors can influence teaching effectiveness. The novelty of this study lies in its focus on the interplay between these variables, contributing to a nuanced understanding of teacher performance dynamics. The implications that educational institutions should adopt a holistic approach to teacher support, recognizing the interconnectedness of stress, satisfaction, and motivation to foster an environment conducive to improved educational outcomes. Highlights: Significant combined effect of stress, satisfaction, and motivation on performance. No significant individual effects found for each variable. Emphasis on interconnectedness for enhancing teacher support. Keywords: Stress, Job Satisfaction, Work Motivation, Teacher Performance, Education